PELAYANAN IBADAH HAJI KHUSUS MELALUI TRAVEL DI KOTA MAKASSAR - Febriansyah, Muh. Darmawan Tri; Samin, Sabri (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The increasing number of pilgrims every year encourages the renewal of regulations, one of which is through the Regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 23 of 2016 concerning the Implementation of Special Hajj. This study aims to find out how the service mechanism and standards for determining costs and sanctions for travel that violates the implementation of special hajj in Makassar City. The research uses qualitative methods with data sources in the form of primary data and secondary data. The results showed that ritually, the implementation of special pilgrimages is no different from regular pilgrimages, which distinguishes only in service standards such as facilities and relatively faster waiting times. Differences in service standards result in high special hajj costs when compared to regular hajj. As an authoritative institution, the Ministry of Religious Affairs has regulated the mechanism for implementing special hajj and there are sanctions for travel that commits violations, such as written sanctions, suspension sanctions to the revocation of permits adjusted to the level of violations committed by travel.